1985
DOI: 10.1161/01.res.56.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine in coronary blood flow regulation after reductions in perfusion pressure.

Abstract: SUMMARY. We employed intracoronary infusion of adenosine deaminase to test the hypothesis that endogenous adenosine contributes to regulation of coronary blood flow following acute reductions in coronary artery pressure. In 16 closed-chest anesthetized dogs, we perfused the left circumflex coronary artery from a pressurized arterial reservoir and measured coronary blood flow following changes in perfusion pressure before and 10 minutes after the start of intracoronary adenosine deaminase, 5 U/min per kg body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(23 citation statements)
references
References 33 publications
4
19
0
Order By: Relevance
“…Schrader et al 36 found that coronary venous levels of adenosine and inosine in the saline-perfused guinea pig heart increased at reduced arterial pressures. On the other hand, Dole et al 37 found that adenosine deaminase infused into the blood-perfused dog myocardium moderately reduced the magnitude of reactive hyperemia but did not significantly affect autoregulation. Hanley et al 38 also found that adenosine deaminase did not attenuate autoregulation the blood-perfused dog heart.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Schrader et al 36 found that coronary venous levels of adenosine and inosine in the saline-perfused guinea pig heart increased at reduced arterial pressures. On the other hand, Dole et al 37 found that adenosine deaminase infused into the blood-perfused dog myocardium moderately reduced the magnitude of reactive hyperemia but did not significantly affect autoregulation. Hanley et al 38 also found that adenosine deaminase did not attenuate autoregulation the blood-perfused dog heart.…”
mentioning
confidence: 97%
“…56 and causes arteriolar constriction in the rat mesoappendix, 37 rat cremaster, 23 and cat mesentery. 58 In the rat mesoappendix and rat cremaster the constriction to venous pressure elevation is greatest in the terminal region of the arteriolar network where the pressure rise would presumably also be greatest.…”
mentioning
confidence: 98%
“…When coronary perfusion pressure is reduced, adenosine is reported to increase to maintain coronary blood flow, 27 suggesting the role of adenosine in coronary autoregulation. However, adenosine deaminase does not affect vascular resistance during graded reduction in perfusion pressure, 45 indicating that adenosine does not play a role in autoregulation of coronary blood flow. Similar results were obtained by blocking the adenosine receptors with theophylline.…”
Section: Role Of Adenosine In Autoregulation Of Coronary Blood Flowmentioning
confidence: 99%
“…Similar results were obtained by blocking the adenosine receptors with theophylline. In fact, since intra-arterially administered adenosine deaminase was detected in cardiac lymph, 45 it is probable that infused adenosine deaminase is distributed in the interstitial space. 46 Other observations suggest that the interstitial adenosine concentration may be too low to elicit vasodilation 47 and that the concentration does not change during autoregulation.…”
Section: Role Of Adenosine In Autoregulation Of Coronary Blood Flowmentioning
confidence: 99%
“…We [20,44] and others [10,11,45] previously demonstrated that adenosine also plays a physiological role in regulating coronary resting flow in human [11], swine [10], dogs [45], guinea pigs [46], and mice [20,44], while some other groups failed to observe an endogenous role of adenosine [3,47,48], which leaves this scientific topic controversial. This discrepancy may be due to different animal models, differences in species, and/or different agonists and antagonists applied in these studies [19].…”
Section: Adenosine-induced Increase In Coronary Flow Is Mediated In Pmentioning
confidence: 99%